2020
DOI: 10.3892/ol.2020.12365
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of competing endogenous RNA network of MCF‑7 breast cancer cells based on the inhibitory effect of 6‑thioguanine on cell proliferation

Abstract: Previous research has proven that 6-thioguanine (6-TG) inhibits the growth of MCF-7 breast cancer cells. Accumulating evidence indicates that long non-coding (lnc)RNAs are involved in the development of various cancer types as competitive endogenous (ce)RNA molecules. The present study was conducted to investigate the regulatory mechanism underlying the function of lncRNAs as ceRNA molecules in MCF-7 cells and to identify more effective prognostic biomarkers for breast cancer treatment. The expression profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…MIR22HG is a tumor suppressor and high MIR22HG was associated with increased OS in BC samples in an analysis of data from TCGA database [ 210 ]. MIR22HG was suggested to be a ceRNA for miR-424 [ 211 ]. Network analysis showed ERRα regulating MIR22HG and LINC-PINT ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…MIR22HG is a tumor suppressor and high MIR22HG was associated with increased OS in BC samples in an analysis of data from TCGA database [ 210 ]. MIR22HG was suggested to be a ceRNA for miR-424 [ 211 ]. Network analysis showed ERRα regulating MIR22HG and LINC-PINT ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…So far, only 4 arlncRNAs (LINC00665, [ 34 , 35 ] PCED1B-AS1, [ 36 , 37 ] LINC00324, [ 38 ] and ZEB1-AS1 [ 39 ] ) have been biologically validated in other tumors. However, as far as we know, these 9 arlncRNAs have not been fully validated in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR results showed that after 6-TG treatment of MCF-7 cells, the expression level of miR-424-5p was decreased and regulated specifically by GADD45G and CCND3 to change the apoptosis and cell cycle of the breast cancer cells. The effect of 6-TG therapy on MCF-7 breast cancer cells establishes a theoretical foundation for the further study of the molecular mechanism of breast cancer regulation and the screening of potential therapeutic targets [ 104 ].…”
Section: Mir-424-5p and Chemotherapymentioning
confidence: 99%